KEJADIAN SICK BUILDING SYNDROME DI INDONESIA : KAJIAN PUSTAKA - Hidayati Alwi; Yuliani Setyaningsih; Ida Wahyuni (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2020)
Background: Sick Building Syndrome (SBS) is a health disorder in the form of symptoms that are followed by discomfort with the environment and odor complaints due to environmental conditions that do not meet the requirements and there is pollution in the room, can be in the form of fungi, microbes, and chemicals. Poor air quality can have a negative impact on workers or employees in the form of complaints of health problems. Objectives: This study aimed to analyzing the incidence of SBS in Indonesia. Research Metodes: The method used in this research was the literature study. The literatures were conducted online through several trusted websites or internet sites. This research was conducted on 15 articles consisting of 9 national articles and 6 international articles. Articles were analyzed bivariately and processed through stages in the form of editing, organizing, analizing and dissemination. Results: The results of the study of 15 articles, showed there was a relationship between physical factors (temperature, humidity, air flow, lighting, noise and ventilation quality), chemical factors (CO2 and CO), biological factors (germs) work stress factors (workload and work pressure), and individual factors (age, years of service, gender and smoking habits) and found no correlation between physical factors (dust) and biological factors (mold) with the occurrence of SBS. Conclusion: the incidence of Sick Building Syndrome in Indonesia is still commonly found, especially in the building where employees work.